Global solar energy use and social viability in Malaysia - Hossain, M.S.; Rahim, N.A.; Solangi, K.H.; Saidur, Rahman; Fayaz, H.; Madlool, N.A. (2011)
Along with the enhancement of technology and alarming of global warming, various types of technologies are advanced worldwide nowadays to harness the energy from the sun such as solar thermal energy, ocean thermal energy conversion, solar ponds, solar tower and photovoltaic systems to utilize the energy in the majority of domestic applications and industrial sector to a certain extent. Subsequently, gradual increase usage of solar energy requires creating awareness among public to protect the environment in term of green campaign which is one of the hot topics among the Malaysians where there are many organizations organizing green campaign such as Environmental Protection Society Malaysia (EPSM), Malaysia Environment NGOs (MENGO) and Treat Every Environment Special Sdn. Bhd. (TRESS). Therefore, this study examines solar energy production and consumption worldwide by looking at various existing solar technologies to have the understanding of each technology. This article also intends to catch up specifically the social viability of solar energy production and use, with the availability of the resources for the full scale development.